Efficacy of photobiomodulation for reducing pain in patients who have sustained fractures. A systematic review - Sánchez-Lozano, Jesús; Martínez-Pizarro, Sandra (Revista Colombiana de Ortopedia y Traumatología, 2025)
Introduction: Fractures are painful and disabling injuries that can be caused by trauma. In recent years, photobiomodulation has been suggested to reduce pain in these patients. Objective: To perform a systematic literature review on the efficacy of photobiomodulation to reduce pain in patients who have sustained fractures. Methodology: A systematic search was performed in PubMed, Cinahl, PsycINFO, SPORTDiscus, Academic Search Complete, Lilacs, IBECS, CENTRAL, SciELO, and WOS. Randomized clinical trials (RCTs) evaluating the efficacy of photobiomodulation in reducing pain in patients with fractures published in English and Spanish within the last 5 years were included. Results: Five RCTs were included (182 patients in total) and all compared photobiomodulation with sham photobiomodulation or placebo. Fracture localization varied between studies: zygomaticomaxillary complex, distal radius, mandible, tibia and/or ankle, and various sites in lower limbs). The duration of therapy ranged from 4 to 8 weeks and all studies found it to be a safe intervention, with no major side effects. Pain was assessed directly using the Visual Analog Scale or the McGill scale. Moreover, some studies measured pain indirectly by analyzing the use of analgesics. Conclusions: Based on the retrieved evidence, it can be stated that photobiomodulation is effective in reducing pain in patients who have sustained fractures.